EXPLICIT ROLE OF METHANOGENIC CONSORTIUM DEVELOPED FOR IMPROVING THERMOPHILIC BIOMETHANATION OF URBAN WASTE - B.J.YOGESH; A.MICHAEL (International Journal of Pharma and Bio Sciences, 2013)
Land-filling option is drying out with rapid pile up of organic waste in urban areas; the problem can be circumvented with accelerated anaerobic decomposition which can also be a source of valuable bio-fuel. But many municipal anaerobic waste treatment systems fail due to the lack of adequate microbial inoculum and also hampered by the doubts on many aspects of its operation and stability. In this regard biomethanation of the organic fraction of urban waste was carried out in laboratory scale reactors with different inoculum. The interdependence among the anaerobic microbial community which leads to stability in operation was assessed with a set of diverse factors. Influential interplay of various physiochemical factors which includes Volatile fatty acid content, reduction in Chemical oxygen demand, average biogas production, methane content of the bio-fuel, variation in pH, influence of temperature and reduction in total solids content was assessed. The operation instability can be solely attributed to three factors, inadequate methanogenic diversity, differential nature of substrate and variation in temperature. Methanogens were isolated from different inoculum based stable digesters and an consortium was developed. The consortium not only circumvented the loopholes of the individual stable digesters but also demonstrated an enhanced stability, greater biogas yield, more methane content and higher reduction in chemical oxygen demand. To confirm the efficacy of the consortium, a direct equal mixture of various inoculum (bypassing the isolation step) was used for biomethanation process. Though it improved the performance of the digesters, the efficiency exhibited by the explicit role of the consortium was higher. Methanogen cell number was estimated both by direct count using fluorescence microscope and by roll tube technique on enriched media. Tracking individual methanogenic species of the consortium in the due course of organic waste digestion will be further carried out using FISH and immune - molecular techniques for further understanding of complex anaerobic process.